1993
DOI: 10.1021/bi00065a015
|View full text |Cite
|
Sign up to set email alerts
|

Affinity labeling and functional analysis of the primer binding domain of HIV-1 reverse transcriptase

Abstract: Six affinity reagents containing chemically reactive groups, either on the phosphate residue at the 5'-end or on the 5'- or 3'-end internucleoside phosphate linkages of the oligothymidylate primers, were used to covalently modify the human immunodeficiency virus type 1 reverse transcriptase (HIV-1 RT). After covalent binding of these modified primer analogs to the enzyme, the addition of [alpha-32P]dTTP, in the presence of a complementary template, led to elongation of the primer. This reaction was catalyzed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
4
10
0
Order By: Relevance
“…According to Majumdar et al (1988Majumdar et al ( , 1989) and our results (Andreola et al, 1993), HIV-1 RT is able to bind the primer before the template. We have shown that, in the absence of template, HIV-1 RT could correctly recognize the 3'9erminal nucleotide of primers bearing chemically reactive groups at the 5' end.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…According to Majumdar et al (1988Majumdar et al ( , 1989) and our results (Andreola et al, 1993), HIV-1 RT is able to bind the primer before the template. We have shown that, in the absence of template, HIV-1 RT could correctly recognize the 3'9erminal nucleotide of primers bearing chemically reactive groups at the 5' end.…”
Section: Discussionsupporting
confidence: 68%
“…The protection of RT by tRNA from modification by reactive analogs of oligonucleotides (Andreola et al, 1993) supports this suggestion. In fact, RT, unlike DNA polymerases, has a specific site for tRNA.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations